Investigation of pathogen distribution, clinical characteristics, and risk factors of neonatal urinary tract infections - Jiang, Bo; Gao, Xiuyi (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the annual variation in pathogen distribution, clinical characteristics, and associated risk factors of neonatal urinary tract infections (UTIs), providing a scientific basis for clinical diagnosis and treatment.MethodsA retrospective analysis was conducted on clinical data from 134 neonatal UTI cases admitted to our hospital between January 2021 and December 2024. The distribution of pathogens, bacterial resistance patterns, clinical manifestations, and laboratory findings were compared in different years. Multivariable logistic regression was employed to identify risk factors associated with neonatal UTIs.Results(1) Among the 134 pediatric patients, 86 were male and 48 were female; 52 (38.8%) were preterm, while 82 (61.2%) were full-term. The incidence rates of UTIs from 2021 to 2024 were 8.2%, 9.1%, 10.3%, and 11.2%, respectively, with a statistically significant difference across the years (P < 0.05). (2) The primary clinical manifestations included fever (72 cases, 53.7%), crying (65 cases, 48.5%), and poor feeding (58 cases, 43.3%). (3) From 2021 to 2024, the detection rate of Gram-negative bacteria exhibited a significant downward trend (75.8%, 70.3%, 65.1%, and 61.2%, P < 0.05), with Escherichia coli showing a yearly decline (P < 0.05). Conversely, the detection rate of Gram-positive bacteria demonstrated a significant upward trend (18.2%, 24.3%, 28.6%, and 32.7%, P < 0.05), with coagulase-negative staphylococci increasing annually (P < 0.05). (4) The detection rate of Gram-positive bacteria was significantly higher in the low birth weight group than in the normal birth weight group (P < 0.05). (5) The antibiotic resistance rates of E. coli and Enterococcus faecium showed a progressive increase over the study period (P < 0.05). (6) Multivariable analysis identified low birth weight (OR = 2.831, 95% CI: 1.562–5.121), indwelling urinary catheter (OR = 3.452, 95% CI: 1.891–6.282), and maternal infection during pregnancy (OR = 2.154, 95% CI: 1.233–3.762) as independent risk factors for neonatal UTIs.ConclusionThe incidence of neonatal UTIs shows a progressive upward trend in recent years, accompanied by a significant shift in pathogen spectra. Particular attention should be given to high-risk factors such as low birth weight and indwelling urinary catheters, necessitating targeted preventive measures.